Profil Kuman Pada Penderita Omsk Dengan Kultur Swab Di Rs Haji Medan - Sofi Tamara Lubis; Siti Masliana Siregar; Fani Ade Irma; Annisa Annisa (ANATOMICA MEDICAL JOURNAL | AMJ, 2020)
Introduction: Chronic suppurative otitis media (CSOM) is a chronic inflammation or infection of the middle ear which is indicated by a tympanic membrane perforation and otorrhea occurring over 2 months of repetitive or persistent settling. The aim of this study is to know the the most common bacteria occured in CSOM. Methods: This was a descriptive cross-sectional study. The subjects consisted of all CSOM patients in October 2017 to December 2017 period who met inclusion criterias Results: There was 27 patients included in this study which consisted of  21 (77.8%) men and 6 (22.2%) women. The age range of <10 years was 21 (77.8%) subjects. Staphylococcus aureus is the most common bacteria presented in CSOM which was 10 (37%) subjects. Proteus sp was the  most common bacteria presented in the age range of  <10 year.  Conclusion: bacterias identified in CSOM are Proteus sp., Staphylococcus aureus, Streptococcus, Pseudomonas auregenosa, and Aerobacter.Keywords: bacteria, CSOM, Sthaphylococcus